Reaming in treatment of non-unions in long bones: cytokine expression course as a tool for evaluation of non-union therapy - Westhauser, Fabian; Zimmermann, Gerald; Bruckner, Thomas; Schmidmaier, Gerhard; Moghaddam-Alvandi, Arash (Archives of orthopaedic and trauma surgery, 2015)
The analysis of peripheral serum cytokine expression patterns has been shown to be a possible method for demonstrating changes in bone metabolism. The aim of this study is to evaluate the effectiveness of this method within the treatment of long bone non-union with intramedullary reaming, a well-established non-union treatment concept.Materials and methodsThree groups were added to this study: group one (G1) suffered from long bone non-unions, treated successfully with intramedullary reaming; group two (G2) consisted of long bone fractures with proper fracture healing; and group three (G3) included long bone fractures resulting in non-unions. We took blood samples on day 2, and after week 1, 4, 6, month 3 and 6 after initial treatment. Clinical and radiological follow-up were provided for 6 months. We measured transforming growth factor ß-1 (TGFß-1), platelet-derived growth factor (PDGF-AB), and insulin like growth factor-1 (IGF-1) at all-time points.ResultsTGF-ß1 levels in G1 and G2 increased from day 2 to 6 weeks after surgery. In general, G1 and G2 showed parallel TGF-ß1 expression patterns, and G3 had a significant peak during first week compared to G1 (p = 0.023). PDGF peaked in G3 during first week after treatment, whereas G1 had its maximum after 4 weeks and G2 after 6 weeks. We were able to detect a significantly lower PDGF concentration at 3 months in G1 compared to G3 (p = 0.029). IGF-1 showed a peak concentration in G1 during the first 4 weeks. Afterwards, concentration levels in both G1 and G2 were higher.ConclusionsOur study was able to show that the cytokine expression pattern in physiological bone healing is similar to that in successful non-union treatment with intramedullary reaming. Our results show that the effect of non-union therapy could be observed objectively by measuring cytokine expression patterns in peripheral blood even in a small group of patients.
Gesehen am 21.02.2017